Library and information university education figures in Spain: 2016 - De-la-Moneda, Mercedes (Anuario ThinkEPI, 2018)
A picture is presented of the state of library and information university education in Spain. Statistical data is provided about both the number and type of the university education describing existing institutions, degree levels and providing data on student enrolment and teachers.